Agriculture–nutrition linkages: A preliminary investigation for rural India. (December 2017) - Balaji, SJ; Jhajhria, Abimanyu; Kumar, Sant; Immanuelraj, T Kingsly; Kar, Amit
Exploring linkages between agriculture, nutrition and human health has become an emerging field of research. Literature shows us both positive and negative externalities of agriculture on nutrition and health. Hence, the first step towards exploring agriculture–nutrition linkages would be 'establishing' the relationship between agriculture and nutrition, and thereby human health. This study, while doesn't explicitly model and estimate complex linkages, attempts to study the direction, strength and magnitude of agriculture on nutritional status in rural India. Using a panel data covering 1991–2012, the study explores the linkages at two stages. Analysis indicates a 'positive causality' of agriculture on human nutrition and the ordinary least squares estimates provide evidence for it. Fixed effects estimates confirm the 'positive causality' after controlling for the effects of several factors. The study concludes that agriculture has a significant positive influence on nutrition, and thereby on health.